2015
DOI: 10.1589/jpts.27.619
|View full text |Cite
|
Sign up to set email alerts
|

Core strength training for patients with chronic low back pain

Abstract: [Purpose] Through core strength training, patients with chronic low back pain can strengthen their deep trunk muscles. However, independent training remains challenging, despite the existence of numerous core strength training strategies. Currently, no standardized system has been established analyzing and comparing the results of core strength training and typical resistance training. Therefore, we conducted a systematic review of the results of previous studies to explore the effectiveness of various core st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
85
1
8

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(104 citation statements)
references
References 23 publications
(85 reference statements)
0
85
1
8
Order By: Relevance
“…Various problems occur in the somatosensory system of patients with chronic low back pain. Decrease of the mobility and stability of the waist occurs in these patients, and these bring about a decline of muscle strength and coordination capability and a change in proprioception6, 7 ) . These disabilities of the musculoskeletal system affect balance performing ability and limit use of a proper exercise strategy in perturbation3 ) .…”
Section: Introductionmentioning
confidence: 99%
“…Various problems occur in the somatosensory system of patients with chronic low back pain. Decrease of the mobility and stability of the waist occurs in these patients, and these bring about a decline of muscle strength and coordination capability and a change in proprioception6, 7 ) . These disabilities of the musculoskeletal system affect balance performing ability and limit use of a proper exercise strategy in perturbation3 ) .…”
Section: Introductionmentioning
confidence: 99%
“…4 Yet that significance was absent when core exercise was compared with general low back exercise. 4 Other investigators 5 have suggested clinicians should focus on interventions that improve disability and have noted improvements in LBP patients who perform some kind of core exercise.…”
mentioning
confidence: 99%
“…3 Patients are more likely to perceive the effectiveness of core exercises than that of other painreduction methods. 5 Decreased pain and increased function in the early stages of intervention may help the patient associate the rehabilitative experience with improvement in the condition. This can demonstrate the value of the patientclinician relationship and lead to increased compliance with all prescribed interventions.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A terhesség alatt szétnyílt egyenes hasizom a core izmait is gyengévé teszi, mivel azok közvetlen kapcsolatban állnak vele, ami idővel az alsó háti szakasz fájdalmához vezethet (Gitta et al, 2017), illetve erősítése segíthet megszabadulni a fájdalmaktól (Franca et al, 2010;Chang, 2015). Úgyszintén megterhelhetik a gerincet a terhességet megelőző évek során megszokásból berögzült rossz ülő, álló pozíciók és a hajlongás, a terhesség maga pedig már könnyen túlterhelheti ezt az amúgy is megviselt gerincet.…”
Section: Bevezetésunclassified